Unquiet understanding : Gadamer's philosophical hermeneutics - Davey, Nicholas, 1950- (SUNY series in contemporary continental philosophy., 2006)
"In Unquiet Understanding, Nicholas Davey reappropriates the radical content of Gadamer's philosophical hermeneutics to reveal that is offers a powerful critique of Nietzsche's philosophy of language, nihilism, and post-structuralist deconstructions of meaning. By critically engaging with the practical and ethical implications of philosophy hermeneutics, Davey asserts that the importance of philosophical hermeneutics resides in a formidable double claim that strikes at the heart of both traditional philosophy and deconstruction."--Jacket.